Answer:
i think it would be d.

Thw average stone on the lowest level of the great pyramid in Egypt was a rectangular prism 5 feet long by 5 feet high by 6 feet deep and weighed 15 tons what was the volume of the average stone how much did one cubic foot of this stone weigh

Someone help meeeeee!!!

How to divide 8/9?:)

16 centimeters to 44.2 centimeters percent of change

1+4=5 2+5=12 3+6=21 8+11=?

Someone help meeeeee!!!

How to divide 8/9?:)

16 centimeters to 44.2 centimeters percent of change

1+4=5 2+5=12 3+6=21 8+11=?

**Answer:**

**8.43**

**Step-by-step explanation:**

easy

8.43 hope this helps :)

f(x) | 9 | -2 | -5 | -1 | 1 | 11

Find the following values:

f^-1 (-2)=

f^-1 (-1)=

**Answer: **The correct answers are:

**- f^{-1}(-2)=3**

**- f^{-1}(1)=0**

**Step-by-step explanation:**

* Since f^{-1} receives inputs from f's range and maps them to their corresponding elements in f's domain, we can reverse the rows in the table as follows to obtain the inputs and outputs of f^{-1}.

* From this table we see that f^{-1}(-2)=3 and that f^{-1}(1)=0.

*** Therefore, the correct answers are****f^{-1}(-2)=3 and f^{-1}(1)=0**

The required **values **f⁻¹(-2) = 3, f⁻¹(-1) = 18, obtained by swapping the input and output values in the inverted table.

To find the inverse of the** function**, can swap the input and output values in the given table.

Then, you can use this inverted table to find the values of the inverse function for specific inputs.

As per the table values are,

x | 5 | 3 | 1 | 18 | 0 | 9

f(x) | 9 | -2 | -5 |-1 | 1 | 11

The values in the **inverted** table are,

f⁻¹(x) | 9 | -2 | -5 |-1 | 1 | 11

x | 5 | 3 | 1 | 18 | 0 | 9

Now, to find the values of the inverse function:

f⁻¹(-2): Looking at the inverted table, when f⁻¹(x) = -2, the corresponding input x is 3. Therefore, f⁻¹(-2) = 3.

f⁻¹(-1): Similarly, when f⁻¹(x) = -1, the corresponding input x is 18. Therefore, f⁻¹(-1) = 18.

Therefore, the **values** in the inverted table are f⁻¹(-2) = 3 and f⁻¹(-1) = 18 .

learn more about **values** here

#SPJ3

The distance the ships traveled are like the legs of a triangle and the question wants to know the hypotenuse. To find the hypotenuse, use the pythagorean theorem. this is a^2 + b^2 = c^2, with a and b being the legs and c being the hypotenuse.

Plug in known values:

84^2 + 62^2 = c^2

Solve:

84^2 = 7056

62^2 = 3844

7056 + 3844 = c^2

7056 + 3844 = 10900

10900 = c^2

Now you just need to isolate c by finding the square root of both sides.

√10900 = 104.403

√c^2 = c

So**c = 104.403**, or just **104.40** when rounded to the nearest tenth.

And if**c is 104.40**, then that means the **hypotenuse is 104.40**.

And all of that basically means that the**di****stance between the ships is 104.40 miles.**

Plug in known values:

84^2 + 62^2 = c^2

Solve:

84^2 = 7056

62^2 = 3844

7056 + 3844 = c^2

7056 + 3844 = 10900

10900 = c^2

Now you just need to isolate c by finding the square root of both sides.

√10900 = 104.403

√c^2 = c

So

And if

And all of that basically means that the

Well, it takes one ball of wool to make 2 knitted caps. So it will take 3 balls of wool to make 6.

since there are 4 wool balls that make 8 caps the ratio is 4:8 or 1:2 ...every ball makes 2 caps there fore your answer is 3 balls of wool will make 6 caps

**Answer:**

**Step-by-step explanation:**

a 0.4

b 0.03

do it like this

**Answer:**

A. 4 tenths or 0.4

B. 5 hundredths or 0.05

C. 30 units or 30

D. 4 units or 4

E. 7 tenths or 0.7

F. 6 hundredths or 0.06

G. 4 thousandths or 0.004

H. 9 hundred or 900

I. 1 hundredth or 0.01

J. 9 thousandths or 0.009

K. 5 tenths or 0.5

L. 6000 units or 6000

M. 70 units or 70

N. 1 thousandth or 0.001

O. 3 thousands or 0.003

P. 2 ten thousandths or 0.0002

Q. 4 hundred thousandths 0.00004

**Step-by-step explanation:**

**Answer:**

multiplier

**Step-by-step explanation:**

You get from a distribution. for example 2 (a + b) = (2a) + (2b) which has happened in this problem. It turns out the same if I make a sum of the subsequent parenthesis of a multiplication

**Answer:**

This is called "Distributive Law "

**Step-by-step explanation:**

x(y + z) = xy + xz